Virtues and institutions in Smith: A reconstruction - Emmanuel S. De Dios (University of the Philippines, School of Economics (UPSE), 2021)
I provide a formal explanation of the relationship between the virtues of prudence, justice, and benevolence described by Adam Smith in the Theory of moral sentiments and connect these with the themes Smith subsequently discusses in the Wealth of nations. I contend that the other-regarding concerns Smith discusses as internally held virtues in TMS are presumed addressed instead by formal mechanisms in the WN - particularly the third-party institutions of law and anonymous market exchange.
Keywords: B12; B15; 330; Adam Smith Problem; virtues; institutions; self-interest; altruism